If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-2y) + -1(4x) = 20 Remove parenthesis around (4x) (-2y) + -1 * 4x = 20 Multiply -1 * 4 (-2y) + -4x = 20 Reorder the terms: -4x + (-2y) = 20 Solving -4x + (-2y) = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '(2y)' to each side of the equation. -4x + (-2y) + (2y) = 20 + (2y) Combine like terms: (-2y) + (2y) = 0 -4x + 0 = 20 + (2y) -4x = 20 + (2y) Divide each side by '-4'. x = -5 + (-0.5y) Simplifying x = -5 + (-0.5y)
| 3x^2-4=4 | | 2x+25=25 | | x-0.6x=32 | | sqrt(2x)+13=5 | | x+2x+14=166 | | x-6=2/3+12 | | 5x-48+7x=-12 | | 9m+19m=84 | | 6x-6=0.5x+38 | | 12x-5=30x+1 | | 5x-48+7x=-21 | | 1/7*y=-15 | | 9-72/3 | | (3x^2-13x-10)/(x-5) | | y/7=-15 | | -0.43=0.03x+0.15 | | 2y=10x | | 3.3333333333333333x+20=x+34 | | -5k+123=6k+7 | | 23/4+64/5 | | 23/4+34/5 | | 3*p=-15 | | 45.5a-52=2a-5 | | 0=u^2-54 | | -4z+20=3z+9 | | 51=5x-9 | | 5x+16=7x-14 | | -z+5=3z+9/4 | | (83*.8)+(x*.2)=70 | | 173-6x=30x+17 | | -z+5=(3z+9/4) | | 14-7x=34-14x |